STRATEGI DAKWAH MELALUI KREATIVITAS SANTRI DALAM MEWUJUDKAN ECO PESANTREN DI PONDOK PESANTREN ASY-SYARIFY PANDANWANGI KECAMATAN TEMPEH KABUPATEN LUMAJANG - Zainul Arifin (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
The Eco pesantren program as a model of environmental education in pesantren has attracted the attention of scientists and researchers, and nationally the Ministry of Environment in collaboration with the Ministry of Religious Affairs launched the program on 5-6 March 2008 in Pondok Gede. The purpose of this research is to find out "Iimpleimeintasii Peinitiatatan Kreiatiiviitas Santrii Peisantrein Asy-Syariifiiy in Realizing Eco Peisantrein dii pondok peisantrein Asy-Syariifiiy" This research uses descriptive qualitative methods to understand the implementation or application carried out related to increasing the creativity of Asy-Syarifity Islamic boarding school students. Data obtained through interviews, In-depth interviews will be conducted with Kiai, Ustad and education staff who have experience in the implementation of performance management in this pesantrem. The interview will focus on their understanding of the strategies that have been used and the challenges faced in increasing the creativity of students. In addition, open-ended questions will be used to explore their views and experiences in more depth. Participatory observation will be carried out by researchers by being in the pesantren environment and involved in daily activities. This observation will provide insight into the Iimpleimeintasii Strateigii kreiatiiviitas santrii in realizing Eico Peisantrein dii Pondok Peisantrein Asy-syariifiiy Pandanwangii District Teimpeih Kabupatein Lumajang.then analyzed to identify the creativity of students in realizing eco pesantren antrii Peisantrein Asy-Syariifiiy. The results of this research in realizing eco pesantren through the creativity of students include the activities of beirsiih liingkungan, piikeit harian santrii, and cleaning peikanan which is carried out once a week which is carried out every Friday by the students and also cottage teachers who are supervised and accompanied directly by asatidz and caregivers